Pengaruh Independensi, Pengalaman Kerja, Objektifitas dan Integritas Internal Auditor Terhadap Kualitas Audit (Survey Pada Bank Swasta Nasional Di Wilayah Jawa Barat) - Asep Kuswara (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2020)
Unqualified opinion (WTP) is a statement given oleh independent auditor. Such statement is proclaimed in froud manner and should  be known by public. However, a sound statement given by the auditor does not necessarily mean that the organization is free from corruption, fraud or deceit. The purpose of this research is to examine the significance level of independence, working experience, objectivity and integrity to the audit quality, both partially and jointly. Survey with questionnaire was used during this research. collecting data through questionnaireson the interval auditor in national Banks headquartered in west Java.The sampling technique used purposive sampling approach. Samples were deployed in this study were 100 questionnaires in seven Bank is headquartered in West Java. Data analysis was performed by multiple regression model  This study reveals that independent, working experience, objectivity and joint integrity affect audit quality. This study also reveals that partially, working experience and integrity have significance affect on audit quality, while independence and objectivity have little significance on the audit quality.